the Impact of the Labor Cluster Job Creation Law on the Welfare of Indonesian Workers - Ahmad Assegaf Ega Pratama (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
The welfare of the working or labor community is a right for every individual worker. The workers or laborers have the same rights and wonders. The welfare of workers is basically the responsibility of the government and employers, in this case the responsibility of the government is divided into two, namely the central government and local government, the level of welfare of workers and workers varies in each region this is due to the minimum wage and cost of living in an area. The government brings a solution by passing Law number 11 of 2020 concerning Job Creation to reduce the gap in the gap between UMR wages and welfare at different levels in each region and alleviate economic problems in Indonesia. This study aims to discuss the impact of the job creation law on the welfare of workers in Indonesia. The research method used is descriptive-qualitative,yes ng where efforts to understand the literature process and analyze the existing laws and conclusions of the problems of job creation laws, especially the employment klister which is partly in the public spotlight because of controversial articles. The conclusion from the results of this study is that the impact of the Job Creation Law on the Employment Cluster itself is still reaping pros and cons from the community and the government. This happened because of the ratification of the Job Creation Law (UU) in the labor klister there are several articles that harm workers or workers in Indonesia, the article is about the distribution of wages, leave for workers, contract system, and severance pay received by workers. On the other hand, it is even feared to be a boomerang that can harm the community or labor.